Anthologizing Gwen Flager's plays in southern lesbian theater. Issue 2 (3rd April 2023) - Gunn, Elizabeth S.
Abstract: With limited anthologizing of southern United States lesbian theater, the purpose of this article is twofold: to anthologize the work of Gwen Flager, self-identified southern lesbian playwright and to interpret Flager's work as intentionally disruptive to gender and sexual norms through humor and a centering of southern lesbian identity. Flager is an award-winning playwright with U.S. southern roots. Born in Oklahoma in 1950, she spent many years in Louisiana and Alabama before relocating to Houston, Texas. Member of the Scriptwriters Houston, Dramatists Guild of America, and New Play Exchange, she won the 2017 Queensbury Theater's New Works playwriting competition for her original script, Shakin' the Blue Flamingo, which premiered in 2018 after a 12-month development process. By offering a series of untold stories about and from various perspectives of U.S. southern lesbian characters who navigate southern cuisine, history, identity, race, class, nationalism, and self-realization throughout the late twentieth century, Flager positions her characters and the plays themselves as owners of the best version of southern culture, shifting the center to an oft-marginalized southern lesbian identity.